Avaliação dos efeitos de um programa de ensino informatizado na leitura com compreensão de textos para escolares com dificuldade de aprendizagem - Silva, Ellen Cristina Brandão da (Universidade Federal de São Carlos, 2026)
Reading is an important skill for the personal and social development of the individual. The present study aims to evaluate the effects of Teaching Module 3 – Reading Comprehension of Texts, from the teaching program Learning to Read and Write in Small Steps (ALEPP in Portuguese), on students with reading comprehension difficulties, as well as the effect of this teaching procedure on school tests in Portuguese Language and the application of a social validity questionnaire with teachers and students. For this, two studies were conducted. In both studies, an assessment of word reading skills and text comprehension was employed before and after the teaching procedure, along with a social validity questionnaire administered to students and teachers. In Study 2, the participants’ Portuguese Language school tests were also monitored. In the first study, ten 2nd grade Elementary School I students with difficulties in reading comprehension participated and did Module 3. The data were analyzed individually, and statistical analyses were conducted comparing pre-test and post-test results. In the second study, fourteen 3rd grade Elementary School I students with reading comprehension difficulties participated. They were divided into an Intervention Group (IG), which completed teaching procedure, Module 3, and a Comparison Group (CG), which engaged in reading children’s books. This design was chosen to verify the effect of Module 3 in comparison with another teaching procedure. The assessment instruments used in this study were the same as those in the first study, and the data were statistically analyzed. The results of both studies indicated that Module 3 was effective for teaching reading comprehension, and, in the social validity questionnaire, teachers and students evaluated the research positively and reported academic contributions. In Study 1, a statistically significant difference was found when comparing the pre-test and post-test results of ACoLE 3. In Study 2, within the intervention group, a statistically significant difference was found when comparing the initial test results with the final and maintenance tests of ACoLE 3. Furthermore, in Study 2, within the comparison group, a statistically significant difference was also found when comparing the initial test results with the intermediate, final, and maintenance tests. Regarding the comparison between groups in Study 2, no statistically significant difference was found. In Study 2, about the performance of the groups in Portuguese Language school tests, no statistically significant difference was found between the groups, nor within the comparison group across the school tests. Unlike the intervention group, in which a significant difference was found when comparing the fourth school test results with those of the second and third school tests, suggesting an improvement in student performance in the fourth school test, possibly due to the contribution of teaching procedure, Module 3. However, in the present research, one limitation is the small sample size, and another limitation is that some participants engaged in extracurricular activities offered by the school, which may also have an important role in improving participants’ performance. It is suggested that future studies conduct the intervention with a larger sample of participants and with greater experimental control of variables.
Evaluation of the effects of a computerized teaching program on reading comprehension for schoolchildren with learning difficulties
Keywords: Leitura com compreensão; Procedimento de ensino; Prova escolar; Reading comprehension; Teaching procedure; School test; CIENCIAS HUMANAS::PSICOLOGIA; 4. Educação de Qualidade